Induction, deduction and mammoth trails - Tałasiewicz, Mieszko (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
The paper examines various instances of 'inductionism-deductionism' controversion (e.g. Popper vs Vienna Circle or the formulation of Laudan's argument against realism as pessimistic meta-induction vs. kind of deduction). The thesis is that the form of logical reconstruction of our reasoning (in every-day life as well as in science or meta-science) as induction or deduction is irrelevant as to the rational evaluation of this reasoning. Thus the inductionism-deductionism controversion is claimed vacuous. Instead of formal logic a sort of evolutionary epistemology is called for adequate account, since - as it is argued for - the degree of sensitivity to counterexamples contradicting our theories and hypotheses is a kind of adaptation to environment.